Palatability of micro-encapsulated iron pyrophosphate (Ferfer®) - Siddiqui, Anum Sohail; Ashraf, Tazeen; Imran, Uzma (International Journal of Clinical Trials, 2018)
Background: Iron deficiency is the leading cause of anemia globally and affects 20% of world adult population. The general practice for replacement of iron reserves is oral supplementation. However, the success of this strategy solely depends on drug adherence and compliance. Where many other factors contribute to compliance, the role of taste of the medicine can also not be neglected. The aim of this study is to evaluate the palatability of micro-encapsulated iron pyrophosphate (Ferfer) and compare its taste with previously taken other oral forms of iron supplements. Methods: The study was conducted with 231 female participants of age more than 18 years. Participants had taken one sachet of micro-encapsulated iron pyrophosphate (Ferfer) for the purpose of taste. Questionnaire based on their previous experience of iron supplements and palatability of Ferfer was asked by participants based on 0-10 mm visual analogue scale and 5 point Likert scale evaluating responses at 0 minute, 5 minute, and at 10 minute. Data was analyzed by using SPSS version 23. Results: The women previously taking some others oral form of iron supplementation scored their supplements, a mean taste score is 2.92±2.44 on the VAS. However, micro-encapsulated iron pyrophosphate (Ferfer) received a mean score of 7.66±1.32 immediately after taking it and a score of 7.96±1.37 after 5 minutes on the 0-10 mm VAS. 81.4% patients will recommend their doctors to prescribe FERFER to them in future. Conclusions: Enhanced palatability of micro-encapsulated iron pyrophosphate sachets have resulted in increased compliance to the supplementation regimen among the participants.